Artikel Analisis Faktor Penyebab Dan Dampak Rendahnya Kesadaran Pendidikan Di Desa Kali Sereng - Kamsi, Nurlila; Zulaiha, Evi (Edification Journal : Pendidikan Agama Islam, 2025)
Education is a key factor in improving the quality of human resources and community welfare. However, awareness of the urgency of education remains a challenge in several rural areas, including Kali Sereng Village, B. Srikaton Subdistrict, Musi Rawas Regency. Although educational facilities are available up to the senior high school level, the community’s interest in pursuing higher education remains low. This study aims to describe the level of educational awareness among the people of Kali Sereng Village, identify the factors influencing the lack of such awareness, and explain its impacts on the community’s social and economic life. This research employed a qualitative descriptive method with data collected through observation, interviews, and documentation studies. The research informants consisted of residents, community leaders, and village officials. Data analysis was conducted inductively through data reduction, data presentation, and conclusion drawing. The results reveal that although most residents have completed education up to senior high school, awareness and motivation to pursue higher education remain limited. The factors contributing to low educational awareness include the majority of families having lower-middle income, parents’ occupations that do not require higher education, lack of family support, low learning motivation among children, and the influence of less supportive peer environments. The impacts include limited job opportunities, lower income, lack of productive skills, and low quality of human resources. These findings indicate the need for an integrated intervention involving the village government, educational institutions, families, and the wider community to enhance educational awareness through outreach programs, scholarships, learning motivation, and a shift in mindset that education is a long-term investment.